The tradition of the adoration of the Theotokos in the Orthodox Church - Musxelišvili, Davitʻ, 1928- (Georgian Classics Ser., 2019)
"The collection is intended for readers interested in scientific and religious issues, generally for all humanitarians-philologists, historians, philosophers, theologians, sociologists, etc.-who are interested in the role and traditions of the Church. The title of the proposed publication, "The Tradition of the Adoration of the Theotokos in the Orthodox Church", implies the phenomenon of the Virgin Mary as one of the basic values of mankind. Theotokos teaches us not only to love and to live in peace, but She Herself is a perfect example of these virtues. Tradition of Theotokos' Adoration in the history of mankind is the manifestation of love, compassion and tolerance in different periods of time and in different countries. Apart from the Orthodox, Catholic and Protestant scholars, scientists from Israel had also expressed their desire to participate in the symposium, which had three sessions: theology, history and culture. Over the centuries, Georgia, which had been surrounded by a huge number of enemies, has survived and Georgia's survival is greater than the earthly logic. This can only be explained by the miracle of God. The phenomenon of the Virgin Mary has the greatest place in Georgia. It is the foundation of our national identity. The Georgian nation has always showed respectful adoration to his Patron. Adoration to the Mother of God has been not only gratitude for the grace received from the Heavenly Queen, but also the height and strength of virtues. Unfortunately, in the last centuries, blasphemous power led to the destruction of the tradition of adoration of God and Theotokos. This publication will help a reader to realize that being under the protection of the Mother of God is a great responsibility: a nation that does not know its own responsibility toward God and Theotokos won't move forward and won't be developed on the path of peace and integrity. It will be of a great importance to explain to a reader what the love to God, and therefore to human, means"--